Microbiological quality of community water from tanks, wells, and sanitation companies - Kennedy, Cristel; Estigarribia, Gladys; Paredes, Luz; Espinola, Ahabeli; Mino, Camila; Cano, Maria; Cárdenas, Marian; Rodriguez, Eliana; Robadin, José (Medicina Clínica y Social, 2025)
Introduction: Microbiologically unacceptable community water may pose a risk to the health of citizens. Objective: To evaluate the microbiological quality of community water samples in urban facilities. Methodology: A cross-sectional analytical study using non-probability convenience sampling. Water samples from 100 community facilities were processed from sources such as wells, tanks, and sanitation companies. Microbiological quality was assessed by counting mesophilic aerobic bacteria and determining the presence of pathogenic microorganisms. Isolated pathogens were identified, and their antibiotic susceptibility profiles were determined. The chi-square test was used for statistical analysis of the relationship between variables. Results: The most common type of water source was artesian wells in 50% of cases; the type of facility from which the most samples were collected was family homes in 40% of cases. Microbiological quality was acceptable in 56% of cases and unacceptable in 44%. The most common cause of unacceptability was the presence of pathogens. The most frequently isolated pathogens were Pseudomonas aeruginosa in 14% of samples and Klebsiella aerogenes in 8% of samples. The isolated pathogens demonstrated broad antibiotic susceptibility and were negative for extended-spectrum beta-lactamases and carbapenemases. Microbiological quality was statistically associated with the water source (p value 0.000). Conclusion: Although the majority of community water tested was microbiologically acceptable, the frequent isolation of pathogens in artesian wells requires corrective measures